2009
DOI: 10.2106/jbjs.g.01483
|View full text |Cite
|
Sign up to set email alerts
|

Motion of the Shoulder Complex During Multiplanar Humeral Elevation

Abstract: Overall shoulder motion consists of substantial angular rotations at each of the four shoulder joints, enabling the multiple-joint interaction required to elevate the arm overhead.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
450
4
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 551 publications
(502 citation statements)
references
References 33 publications
(68 reference statements)
35
450
4
13
Order By: Relevance
“…The present study also demonstrated that scapular internal or external rotation differed significantly according to the plane of elevation, The scapula was internally rotated during flexion, with no change compared to its resting position during scapular plane elevation, and it was externally rotated during abduction. Similar effects dependent on the plane of elevation have been described, with the scapula reportedly internally rotated by an average of 7° during flexion compared to scapular plane elevation and externally rotated by an average 7.5° during abduction compared to scapular plane elevation 4) . However, that study combined data obtained from both men and women.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…The present study also demonstrated that scapular internal or external rotation differed significantly according to the plane of elevation, The scapula was internally rotated during flexion, with no change compared to its resting position during scapular plane elevation, and it was externally rotated during abduction. Similar effects dependent on the plane of elevation have been described, with the scapula reportedly internally rotated by an average of 7° during flexion compared to scapular plane elevation and externally rotated by an average 7.5° during abduction compared to scapular plane elevation 4) . However, that study combined data obtained from both men and women.…”
Section: Resultssupporting
confidence: 70%
“…It is commonly thought that the collapse of scapulohumeral rhythm may predict glenohumeral dysfunction 3,5,11) . Upward rotation, posterior tilt, and internal rotation of the scapula reportedly increase with glenohumeral elevation, and the internal and external rotation angles differ significantly between the planes of elevation during glenohumeral flexion, scapular plane elevation, and abduction 4) . Many previous studies of scapular kinematics have considered various planes of elevation and tasks.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Except for the medial rotation, the values reported by Ludewig et al 25 are similar to those found in this study, in which the effect of the movement of sensors on the skin of volunteers on the values found was considered minimum.…”
Section: Discussionsupporting
confidence: 89%
“…Ludewig et al 25 found similar results with values of 5° of upward rotation, 41° of medial rotation and 13° of anterior tilt in a sample of healthy subjects and using electromagnetic sensors attached to pins transcortically inserted into the bones of the shoulder complex 25 . Except for the medial rotation, the values reported by Ludewig et al 25 are similar to those found in this study, in which the effect of the movement of sensors on the skin of volunteers on the values found was considered minimum.…”
Section: Discussionmentioning
confidence: 70%